2019
DOI: 10.1182/blood.2019000854
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of BTK and PLCG2 mutations in a real-life CLL cohort still on ibrutinib after 3 years: a FILO group study

Abstract: Mutational analyses performed following acquired ibrutinib resistance have suggested that chronic lymphocytic leukemia (CLL) progression on ibrutinib is linked to mutations in Bruton tyrosine kinase (BTK) and/or phospholipase Cγ2 (PLCG2) genes. Mutational information for patients still on ibrutinib is limited. We report a study aimed to provide a “snapshot” of the prevalence of mutations in a real-life CLL cohort still on ibrutinib after at least 3 years of treatment. Of 204 patients who initiated ibrutinib vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 23 publications
(31 reference statements)
0
87
0
1
Order By: Relevance
“…29 Ahn et al 30 BTK-and PLCG2-mutations in a real-life setting, evaluated by next-generation sequencing, have been reported by the French Innovative Leukemia Organization, respectively in 57% and 13% patients who received ibrutinib. 31 This finding was significantly associated with subsequent CLL progression at a median of 8.5 months after sample collection. In the light of the above observations it would be important to consider future clinical trials aimed at evaluating the clinical impact of an early switch to another treatment in patients carrying BTK mutations and trials of agents capable of overcoming ibrutinib resistance caused by acquired BTK or PLCG2 mutations are already in progress.…”
Section: Resistance To Ibrutinibmentioning
confidence: 87%
See 1 more Smart Citation
“…29 Ahn et al 30 BTK-and PLCG2-mutations in a real-life setting, evaluated by next-generation sequencing, have been reported by the French Innovative Leukemia Organization, respectively in 57% and 13% patients who received ibrutinib. 31 This finding was significantly associated with subsequent CLL progression at a median of 8.5 months after sample collection. In the light of the above observations it would be important to consider future clinical trials aimed at evaluating the clinical impact of an early switch to another treatment in patients carrying BTK mutations and trials of agents capable of overcoming ibrutinib resistance caused by acquired BTK or PLCG2 mutations are already in progress.…”
Section: Resistance To Ibrutinibmentioning
confidence: 87%
“…BTK‐ and PLCG2‐mutations in a real‐life setting, evaluated by next‐generation sequencing, have been reported by the French Innovative Leukemia Organization, respectively in 57% and 13% patients who received ibrutinib . This finding was significantly associated with subsequent CLL progression at a median of 8.5 months after sample collection.…”
Section: Resistance To Ibrutinibmentioning
confidence: 93%
“…Genetic mechanisms of primary or acquired resistance to ibrutinib have been widely studied and recurrent mutations associated with resistance have been described in B cell malignancies ( Table 1 , Figure 1 ). Whole-exome sequencing revealed mutations in BCR-involved proteins BTK and PLCγ2 in ~80% of CLL patients with acquired resistance to ibrutinib ( 7 , 96 ), however, some studies have reported a much lower frequency of these mutations ( 97 , 98 ). The most common mutation in BTK is a C481S point mutation which interferes with the binding of ibrutinib to BTK ( 7 , 68 ).…”
Section: Genetic Mechanisms Of Ibrutinib Resistancementioning
confidence: 99%
“…In 2014, a study using whole-exome sequencing discovered acquired mutations within the BTK gene in 5/6 high-risk CLL patients relapsing on ibrutinib (10). A recent study on 30 CLL patients with residual lymphocytosis treated with ibrutinib for 3 years confirmed the presence of BTK mutations in 57% of CLL patients, and the presence of BTK mutations was associated with subsequent relapse (11). A number of studies have confirmed the presence of this mutation in CLL patients relapsing on ibrutinib and have shown that those mutations were not present prior to drug administration (12)(13)(14).…”
Section: Resistance-associated Mutations In Ibrutinib Treatmentmentioning
confidence: 99%
“…Moreover, different PLCG2 mutations are usually found in multiple subclones with low allelic burden (12,13,17). A recent study confirmed PLCG2 mutations in 13% of ibrutinib treated patients with residual lymphocytosis (11). However, the exact contribution of the PLCG2 to the clinical resistance of CLL patients remains not fully understood (22).…”
Section: Resistance-associated Mutations In Ibrutinib Treatmentmentioning
confidence: 99%